Legal Protection for Foreign Investors at Normative and Implementation Levels in Indonesia - Hasim Sukamto; Hulman Panjaitan; Paltiada Saragi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Foreign direct investment (FDI) has a strategic role in Indonesia's economic development. However, the realization of foreign investment is not free from challenges related to legal certainty and protection. This study aims to analyze legal protection for foreign investors in Indonesia, both in terms of applicable legal norms and from the aspect of implementation in the field. Through a literature review, information was collected from various sources in the form of journals, articles, and relevant laws and regulations to gain a broad understanding of legal protection for foreign investors at the normative and implementation levels in Indonesia. The results of the study indicate that Indonesian laws and regulations, especially Law No. 25/2007 concerning Investment, various Bilateral Investment Treaties (BITs), and FTAs ​​provide a comprehensive legal protection framework for foreign investors. In the field, legal uncertainty still arises due to overlapping regulations, frequent policy changes, and different interpretations between institutions. Slow and less transparent licensing bureaucracy, as well as the risk of extortion practices, reduce the attractiveness of investment. Reform efforts such as simplifying licensing through OSS, establishing BKPM as a one-stop shop, and ratifying the Omnibus Law on Job Creation have shown progress in increasing certainty and ease of investment.